Sensory, pH, synaeresis, water-holding capacity, and microbiological changes in homemade yogurt prepared with maca (Lepidium meyenii) powder and propolis extract - OMURTAG KORKMAZ, BURCU İREM (ELSEVIER, 2021)
This study aimed to investigate the effects of maca (Lepidium meyenii) powder and propolis extract supplementation in homemade yogurt. For this purpose, four types of yogurt, including plain yogurt (Y), yogurt with 0.05% propolis (P), yogurt with 5% maca (M), and yogurt containing both 5% maca and 0.05% propolis (MP), were prepared. YC-380 Yo-Flex (R)-encoded Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus were used as starter cultures in pasteurised milk. Samples were stored at 4 degrees C for seven days, and their Lactobacillus counts, pH values, water-holding capacity (WHC) values, and densities were analysed. Lactic acid bacterial counts were calculated using the spread on plate method. Sensory analysis of the yogurts was performed by 10 nutritionist panellists. According to the results of these experiments, Lactobacillus sp. could survive in yogurts without maca (Y and P), which showed the highest Lactobacillus counts. The change in the Lactobacillus counts in the different yogurts during storage was not statistically significant. The pH of MP was significantly the lowest, whereas that of Y was significantly the highest. The pH levels of the different yogurts decreased significantly from day 1 to day 7 (p < 0.05). Synaeresis of the yogurts decreased with time, and this change was significantly higher in Y and P. WHC values of all groups increased significantly, and that of Y was the highest during storage (p < 0.01). The increase in the WHC levels was the highest in P and the lowest in M during storage, suggesting an enhancing effect of propolis on WHC of yogurts. Regarding the sensory assessment of the samples, Y was most acceptable and MP was least acceptable (p < 0.05). The sensory features of the yogurts were affected by the distinct colour and odour of maca, and this could be adjusted by changing the doses of this supplement. However, this study comprised of only short-time storage data, and hence, future studies with longer storage periods are required.
Keywords: Yogurt; Propolis; Maca; Sensory assessment; Lactobacillus sp.